Helicobacter pylori serology and evaluation of gastroduodenal disease in Nigerias with dyspepsia (2004)
Helicobacter pylori (H. pylori) has been strongly associated with various gastroduodenal diseases worldwide with only a few studies emanating from developing countries. The objectives of this study were to determine the prevalence of serum immunoglobulin G (lgG) and underlying gastroduodenal pathology in Nigerian patients with dyspepsia and ascertain the usefulness of H.pylori lgG screening in decreasing endoscopic workload in dyspeptics in Nigeria. fifty-five patients with dyspepsia and 55 age and sex-matched apparently normal control were screened for H.pylori lgG using ImmunocombrII kits. Each of the 55 patients were also examined endoscopically with biopsies taken appropriately. Serology was positive in 94.5% and 92.7% of dyspeptic patients and controls respectivley. Gastroduodenal inflammation was the commonest endoscopic finding, 43 (78.18%). Other findings were malignant gastric tumour 6(10.9%), reflux oesophagitis 3(5.45%), gastric ulcer 2(3.64%), and duodenal ulcer in 1(1.82%). chronic gastritis was the main histopathologic finding in the dyspeptic patients. It is concluded that serum H. pylori lgG cannot be used as a screening procedure to reduce endoscopic workload in Nigerian patients with dyspepsia.